Flap delineation guidelines in postoperative head and neck radiation therapy for head and neck cancers. (October 2020) - Le Guevelou, J.; Bastit, V.; Marcy, P.Y.; Lasne-Cardon, A.; Guzene, L.; Gerard, M.; Larnaudie, A.; Coutte, A.; Beddok, A.; Calugaru, V.; Johnson, A.; Gery, B.; et al.
Highlights: Reconstructive surgery with flaps is used in increasing numbers of patients. Postoperative CTV delineation guidelines have systematically omitted recommendations on flap delineation. Radiotherapy is taken responsible for loss of functional outcomes after surgery with flaps. Flap delineation can help to document dose effects on flaps with respect to radiotherapy. Abstract: Introduction: Reconstructive surgery in head and neck cancers frequently involves the use of autologous flaps to improve functional outcomes. However, the literature suggests that postoperative radiotherapy deteriorates functional outcomes due to flap atrophy and fibrosis. Data on patterns of relapse after postoperative radiotherapy with a flap are lacking, resulting in heterogenous delineation of postoperative clinical target volumes (CTV). Flap delineation is unusual in routine practice and there are no guidelines on how to delineate flaps. Therefore, we aim to propose a guideline for flap delineation in head and neck cancers to assess dose-effects more accurately with respect to flaps. Material and methods: Common flaps were selected. They were delineated by radiation oncologists and head and neck surgeons based on operative reports, on contrast-enhanced planning CTs and checked by a radiologist. Each flap was divided into its vascular pedicle and its soft tissue components (fat, fascia/ muscle, skin, bone). Results: Delineation (body and pedicle) of Facial Artery Musculo-Mucosal, pectoralis, radial forearm, anterolateral thigh, fibula and scapula flaps was performed. Based on information provided in operative reports, i.e. tissue components, size and location, flaps can be identified. The various tissue components of each flap can be individualized to facilitate the delineation. Conclusion: This atlas could serve as a guide for the delineation of flaps and may serve to conduct studies evaluating dose-effects, geometric patterns of failure or functional outcomes after reconstructive surgery. Changes in postoperative CTV definitions might be needed to improve risk/benefit ratio in the future based on surgery-induced changes.